2016
DOI: 10.1186/s12957-016-0854-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transanal tube placement after anterior resection for rectal cancer: a systematic review and meta-analysis

Abstract: BackgroundAnastomotic leakage is a serious complication that can occur after anterior resection of the rectum. There is a question regarding whether the placement of a transanal tube can decrease the rate of anastomotic leakage. The aim of this systematic review and meta-analysis was to evaluate the efficacy of transanal tube placement after anterior resection.MethodsWe searched three major databases (PubMed, Embase, and the Cochrane Library) up until January 2015 for studies evaluating the benefit of transana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…In addition, surgical stoma closure under general anesthesia confers additional stress on patients. A meta-analysis has shown that transanal tube positioning helps to lower the postoperative incidence of AL, hence reducing the necessity for subsequent reoperation [ 38 ]. In contrast, the AL rate was significantly higher in 11 (61%) of the 18 patients who required transanal drainage in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, surgical stoma closure under general anesthesia confers additional stress on patients. A meta-analysis has shown that transanal tube positioning helps to lower the postoperative incidence of AL, hence reducing the necessity for subsequent reoperation [ 38 ]. In contrast, the AL rate was significantly higher in 11 (61%) of the 18 patients who required transanal drainage in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the incidence of anastomotic leakage after such surgery has also increased ranging from 4% to 26% drawing attention to this serious problem. 6,7 Possible factors contributing to this problem include the reduced blood supply of the anorectal remnant and the large pelvic cavity after TME, which predispose to potential fluid accumulation and pelvic infection complicated by poor anastomotic healing post (neo)adjuvant radiotherapy. 8,9 The leak rates are significantly high if there is no diverting ileostomy (44.4% versus 12.7% respectively).…”
mentioning
confidence: 99%
“…Results of both the meta-analysis of the three observational studies and the one randomized trials indicate that placement of a transanal tube significantly decreases the risk of leakage and reoperation [16]. While the mechanism of action of the transanal tube is unclear, it may be related to reduction in endoluminal pressure in the anastomotic portion of the intestine which may be an important factor in anastomotic leakage [17]. Although transanal tube may reduce the risk of anastomotic leakage and reoperation, its placement increases patients' discomfort and inconvenience.…”
Section: Resultsmentioning
confidence: 98%